Mass Spectrometry-Based Rapid Quantitative Bioanalysis of Flibanserin: Pharmacokinetic and Brain Tissue Distribution Study in Female Rats. Issue 6 (4th February 2020) - Sharma, Manish Kumar; Rathod, Rajeshwari; Sengupta, Pinaki
Abstract: Flibanserin (FLB) is the first United States Food and Drug Administration (USFDA) approved serotonin modulator recently marketed to treat acquired generalized women hypoactive sexual desire disorder. The scope of this study was to develop and validate a sensitive, selective and reliable ultra-performance liquid chromatography–mass spectroscopy/mass spectroscopy-based quantification method for FLB in rat plasma as well as brain tissue samples. The method includes a simple liquid–liquid sample extraction procedure. FLB was subjected to chromatographic separation using a poroshell C18 column with the mobile phase comprising a mixture of acetonitrile (ACN), 10 mM ammonium acetate and acetic acid (90:10:0.1, v/v/v). Detection and quantification of FLB after positive electrospray ionization were carried out in selective ion monitoring mode. The fragment ions ( m / z ) of FLB (parent ion: 391.1741) and IS (parent ion: 448.1550) were monitored at 161.0704 and 285.0917, respectively. A linear response of FLB was observed over a concentration range of 2.5–600 ng/mL in plasma and 5–500 ng/mL in brain tissue homogenate. The intra- and inter-day precision and accuracy of the method met the acceptable limits specified in the USFDA bioanalytical method validation guideline. The analyte was found to be stable in benchtop, freeze-thaw, auto-injector and dry extract stability studies. The developed method was used to quantitate FLB in the plasma and brain tissue of a single-dose oral pharmacokinetic and brain tissue distribution study in female rats. Maximum FLB concentration in plasma and brain was achieved within an hour; however, the total amount of the drug that reached the brain was significantly less than in plasma. Rate of elimination of FLB from brain was also faster resulting in a lesser half-life in brain compared to the plasma.